Investigating enhanced Aqua MODIS aerosol optical depth retrievals over the mid‐to‐high latitude Southern Oceans through intercomparison with co‐located CALIOP, MAN, and AERONET data sets. Issue 10 (29th May 2013) - Toth, Travis D.; Zhang, Jianglong; Campbell, James R.; Reid, Jeffrey S.; Shi, Yingxi; Johnson, Randall S.; Smirnov, Alexander; Vaughan, Mark A.; Winker, David M.
Abstract: [1] A band of enhanced aerosol optical depth (AOD) over the mid‐to‐high latitude Southern Oceans exists in some passive satellite‐based aerosol data sets, including Moderate Resolution Imaging Spectroradiometer (MODIS) products. Past studies suggest several potential causes contributing to this phenomenon, including signal uncertainty, retrieval bias, and cloud contamination. In this paper, quality‐assured Aqua MODIS aerosol products in this zonal band are investigated to assess cloud contamination as a cause. Spatially and temporally collocated cloud and aerosol products produced by the Cloud‐Aerosol Lidar with Orthogonal Polarization (CALIOP) project relative to Aqua MODIS AOD in this region are considered. Maritime Aerosol Network (MAN) and Aerosol Robotic Network (AERONET) AOD data are also collocated with Aqua MODIS retrievals for surface context. The results of this study indicate that the high Aqua MODIS AOD are not seen in the CALIOP aerosol products, cannot be screened using active profiling of collocated observations for cloud presence, and are not detected by ground‐based observations such as MAN and AERONET. Enhanced AOD values are attributable primarily to stratocumulus and low broken cumulus cloud contamination, as identified with CALIOP products. But these clouds explain only about 30–40% of the total anomaly. Cirrus cloud contamination is also a factor. However, in contrast to the rest of the globe, they contribute less overall, relative to low‐level liquid water clouds, which are considered likely the result of misidentification of relatively warm cloud tops compared with surrounding open seas. Key Points: A band of enhanced AOD over Southern Oceans (ESOA) is observed by some sensors ESOA is not evident from ground‐based and CALIOP data CALIOP analysis suggests cloud contamination is not only factor in ESOA